A Conceptual Model of Learning Agility and Authentic Leadership Development: Moderating Effects of Learning Goal Orientation and Organizational Culture. (January 2017) - Yadav, Nidhi; Dixit, Shikha
The present article attempts to examine the relationship between learning agility and authentic leadership development. The recent rise in the cases of fraud involving leaders at various levels in the organizations, and the resulting distrust among the employees towards their leaders, points to the need to have authentic leaders, given the positive organizational outcomes associated with this leadership approach. Further, scholars have suggested that leadership development is possible through learning from one's life experiences. The developmental definition of authentic leadership also reflects the importance of learning from past experiences. Yet, studies have largely overlooked to explore the association between learning agility and authentic leadership development. This paper further tries to analyze the moderating effects of learning goal orientation and organizational culture on this relationship. Therefore, based on the existing research, the associations among these factors have been delineated and a conceptual model has been presented along with several propositions. Implications for future research and limitations of this work have also been discussed towards the end.